(untitled) (CIPEEX, 2024)
Tax reform in Brazil is a very important issue, especially in the context of simplifying and modernizing the tax system. The implementation of the VAT/IBS tax (Value Added Tax/Goods and Services Tax) is being discussed as one of the main measures of this reform, with the aim of replacing the current consumption taxes and improving the efficiency and equity of the Brazilian tax system. The aim of this paper is to analyze the implementation of the VAT/IBS tax from the perspective of Tax Reform in Brazil. The research aims to understand the historical, structural and legal implications of the introduction of this new tax and assess its impact on the national tax system. The study used the hypothetical-deductive method, starting from general observations about the Brazilian tax system to the specific analysis of the case of the implementation of VAT/IBS. The research revealed that the historical evolution of taxation in Brazil has been marked by various reforms, each with significant impacts on the country’s tax structure. The 1965 Tax Reform, in particular, played a crucial role in shaping the current tax system. The analysis of consumption taxes showed that the current system is complex and often inefficient, with multiple taxes on the same tax base, generating administrative overload and legal uncertainty. The proposal to implement VAT/IBS, as discussed in the tax reform currently underway, aims to simplify the system by unifying various consumption taxes into a single tax. This new model promises greater clarity, efficiency and legal stability, as well as facilitating cooperation between federal entities. It can be concluded that tax reform is indispensable for Brazil and that simplifying the tax system by implementing VAT/IBS can bring numerous benefits. The introduction of this tax can result in greater clarity and effectiveness in tax benefits, increase cooperation between federal entities and provide greater legal stability for taxpayers. However, for these benefits to be fully realized, careful and well-planned implementation is essential, taking into account the particularities of the Brazilian context. Tax reform, especially with the adoption of VAT/IBS, represents a significant step towards a more modern, fair and efficient tax system, capable of meeting the needs of a growing economy and a society that demands greater fiscal equity.